Can neighborhood green space mitigate health inequalities? A study of socio-economic status and mental health. (March 2016) - Sugiyama, Takemi; Villanueva, Karen; Knuiman, Matthew; Francis, Jacinta; Foster, Sarah; Wood, Lisa; Giles-Corti, Billie
Abstract: This study examined whether the association of psychological distress with area-level socio-economic status (SES) was moderated by the area and attractiveness of local green space. As expected, the odds of higher psychological distress was higher in residents in lower SES areas than those in higher SES areas. However, our results were inconclusive with regard to the moderating role of green space in the relationship between psychological distress and SES. Further investigations incorporating safety and maintenance features of green space and street-level greenery are warranted.